The Influence of Administrative Supervision on Teacher’s Instructional Performance and Students’ Academic Achievement - Lorezo, Marnelli C.; Ramirez, Cybill Ann A. (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study determined the influence of administrative supervision on teachers’ instructional performance and students’ academic achievement at Julio Ledesma National High School. Specifically, it examined supervision practices in terms of classroom observation, mentoring, coaching, and feedback, and their relationship with teaching performance and learner outcomes. A descriptive correlational research design was employed. Data were gathered from teachers handling Grades 9, 10, and 12 of Julio Ledesma National High School, San Carlos City, using validated survey questionnaires, while students’ academic achievement was obtained from school academic records. Statistical tools such as weighted mean and Pearson’s product–moment correlation coefficient were used to analyze the data. The results revealed that administrative supervision was highly practiced and development-oriented. Teachers’ instructional performance was rated as high, whereas students’ academic achievement was generally satisfactory. A strong and significant relationship was found between administrative supervision and teachers’ instructional performance, indicating that effective supervision enhances teaching effectiveness. However, no significant direct relationship was established between administrative supervision and students’ academic achievement, suggesting an indirect influence through improved instructional performance. The study concludes that administrative supervision is essential for strengthening instructional quality and recommends the continued implementation of development-focused supervisory practices to support effective teaching and improved learning outcomes.